Colonists and colonials : animals' protection legislation in New Zealand, 1861-1910 : a thesis submitted in partial fulfillment of the requirements for the degree of Master of Arts in History, Massey University - Aramakutu, Evaan (Massey University, 1997)
The protection of animals in New Zealand may be aptly described as a rapid transition. In less than fifty years, the emphasis of the animals' protection policy completely transformed. The forty-nine years between 1861 and 1910 were, therefore, the busiest and most turbulent period in animals' protection policy's complicated and engaging history. In 1861, the animals' protection policy firmly emphasised the protection of particular imported species. The vast majority of indigenous birds were, therefore, unprotected. Underpinning the protection of animals at that stage was the predominant colonist national sentiment, and their vision of the Britain of the South. By 1910, however, every indigenous bird was protected absolutely in New Zealand unless it was exempted by Order in Council. The reasons for the change in the animals' protection policy were many and varied, but underlying all of them was the colonial adoption of an indigenous national sentiment. Rather than the philosophy that underpinned the protection of animals for policy makers, therefore, it was the national sentiment of colonist and colonial society that was reconstructed. In that respect, the nineteenth-century emphasis that was placed upon the protection of imported species was no different to the development of a twentieth-century native bird conservation ethic.
Keywords: Wildlife conservation; Animal protection, New Zealand; Animal protection policy